2018
DOI: 10.1002/cre2.104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of masticatory performance and tongue pressure between children and young adults

Abstract: The aims of the present study were to evaluate whether there are significant differences in masticatory performance by gender and dental stage. We also determined the factors directly associated with the masticatory performance in children, and those directly associated with masticatory performance in young adults. The study included 180 subjects, ranging in age from 6 to 12 years or 20 to 33 years. The subjects were divided into three groups according to the Hellman developmental stage (III A, III B, or VA); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 23 publications
4
32
0
1
Order By: Relevance
“…Our study found there was a positive correlation between duration of swallowing saliva at posterior tongue and weight as well as BMI, similar to the result of Fujita et al and Ichikawa et al . The former found better masticatory performance is directly associated with a higher BMI.…”
Section: Discussionsupporting
confidence: 91%
“…Our study found there was a positive correlation between duration of swallowing saliva at posterior tongue and weight as well as BMI, similar to the result of Fujita et al and Ichikawa et al . The former found better masticatory performance is directly associated with a higher BMI.…”
Section: Discussionsupporting
confidence: 91%
“…Between 2 and 4 years, functionally balanced mature swallowing prevails; however, the tongue thrust, which is part of the infantile swallowing pattern, may be found in children older than 4 years, and even sometimes in adolescents and adults [48] . In several studies, maximum tongue pressure was directly associated with masticatory performance among children aged 6–12 years [27] , [49] . In addition, tongue pressure and masticatory performance were also positively correlated in young adults [18] , [49] .…”
Section: Relationship Between Masticatory Performance and Tongue Presmentioning
confidence: 99%
“…In several studies, maximum tongue pressure was directly associated with masticatory performance among children aged 6–12 years [27] , [49] . In addition, tongue pressure and masticatory performance were also positively correlated in young adults [18] , [49] . These data suggest that the development of masticatory performance is closely associated with an increase in tongue pressure.…”
Section: Relationship Between Masticatory Performance and Tongue Presmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a pilot study suggested that the mean value of maximum tongue pressure among children with early mixed dentition is approximately 30 kPa (Fujita, Ichikawa, Hamaguchi, & Maki, 2018).…”
Section: Participantsmentioning
confidence: 98%